(untitled) (Nonconventional Technologies Review, 2021)
The paper presents results of the manufacturing process of a porous high-strength glass-ceramic foam using colorless glass waste (between 35.5-50.0%) and coal fly ash (between 24.6-35.5%) as raw materials, sodium borate (between 25.0-28.0%) as a fluxing agent and calcium carbonate (between 0.4-1.0%) as a foaming agent. The heating technique was based on the conversion of microwave energy into heat, the sintering/foaming temperature varying between 802-815 ºC. The characteristics of the glass-ceramic foam samples were: apparent density between 0.38-0.45 g/cm3, porosity between 78.6-81.9%, thermal conductivity in the range 0.049-0.064 W/m·K, compressive strength between 2.5-6.0 MPa and pore size below 0.60 mm. The specific energy consumption had very low values (0.72-0.82 kWh/kg) confirming the high energy efficiency of the predominantly direct microwave heating technique.